Cold-resistant lactic acid bacteria in Jerusalem artichoke silage: quality, microbiome and metabolome dynamics during aerobic exposure on the Qinghai-Tibet Plateau - Wei, Xiaoqiang; Wang, Lihui; Zhang, Haiwang; Tan, Long; Yang, Shipeng; Li, Jiang; Liu, Zhenna; Zhong, Qiwen; Sun, Xuemei (Frontiers in Microbiology, 2026)
Forage scarcity during the cold season poses a major challenge to livestock farming on the Qinghai-Tibet Plateau. Jerusalem artichoke (Helianthus tuberosus) offers a promising alternative, but aerobic exposure of its silage leads to nutrient loss and microbial spoilage under low temperatures. This study aimed to evaluate the effects of inoculating cold-resistant lactic acid bacteria (LAB)—Lactiplantibacillus plantarum GN02 (homofermentative) and Levilactobacillus brevis XN25 (heterofermentative)—on silage quality, microbiome, and metabolome dynamics during aerobic exposure. Silage was prepared from Jerusalem artichoke stems and leaves, treated with sterile water (CK), Lpl. plantarum (YZ), Lv. brevis (YD), or their mixture (YZD), and ensiled for 60 days at −5 to 8 °C. Samples were analyzed at 0, 7, and 14 days of aerobic exposure (−10 to 5 °C) for fermentation parameters (pH, organic acids, dry matter, water-soluble carbohydrates, crude protein, fibers), microbial communities via 16S rRNA and ITS sequencing, and metabolites using LC–MS-based untargeted metabolomics. Inoculation with Lpl. plantarum maintained lower pH (<5), higher lactic acid, dry matter, and water-soluble carbohydrates, while suppressing spoilage bacteria (e.g., Carnobacterium, Citrobacter) and enriching Lactobacillus. Metabolomics revealed upregulated flavonoids and octadecanoids, enhancing antioxidant defenses and downregulating carbohydrate degradation pathways. Lv. brevis accelerated spoilage with elevated pH and nutrient loss, whereas the mixture showed intermediate effects. These findings demonstrate Lpl. plantarum’s efficacy in mitigating aerobic deterioration, providing a theoretical basis for optimizing silage preservation and supporting sustainable livestock production in high-altitude regions.